Biography as an Interpretative Model of Cultural Transfers: The Case of Peter Paul Vergerio the Younger and the Habsburg borderlands - Falski, Maciej (Poznańskie Studia Slawistyczne, 2025)
This article argues for the analytical value of the concept of cultural biography in understanding processes of cultural transfer. Biography is treated here as a social construct that reflects an individual’s functioning within the public sphere, shaped by stable dispositions and social roles. The notion of transfer, in turn, encompasses not only the spread of ideas but also of attitudes, dispositions, and practices, offering a more nuanced framework for describing the formation of cultural communities. The analysis focuses on the life of Pier Paolo Vergerio the Younger (c. 1498–1565), a theologian, publicist, and reformer from Koper in Istria. His biography illustrates the intersection of two cultural models – the humanist and the reformer – and highlights his activity within the cultural borderlands of the Habsburg territories. Vergerio’s connections with Slovenian and Croatian reformers occupy a significant place in the broader history of European culture. The article concludes by proposing cultural biography as a fruitful category for comparative cultural research.